Waiting for markets to change me—High-stakeholders' views of antibiotic use and antibiotic resistance in pig production in Brazil - Albernaz-Gonçalves, Rita; Olmos Antillón, Gabriela; Hötzel, Maria José (Frontiers in Veterinary Science, 2022)
Overuse of veterinary antibiotics is a risk factor for antimicrobial resistance (AMR), which is a global public health emergency. More than 70% of the antibiotics consumed worldwide are used in farm animals, mainly in poultry and pig herds. Brazil is the fourth largest pork producer globally and the second-largest user of antibiotics in animals. Qualitative research can help understand the complexities around antibiotic use (AMU) in Brazilian pig herds and identify stakeholders' attitudes concerning the rational AMU and AMR in the production chain. This study aimed to explore the knowledge and attitudes of high-level professionals in the animal production chain about AMU and AMR in pig farming, the relationship with pig welfare and AMU in Brazil. We conducted 32 in-depth interviews with individuals active in the pig industry. The majority of the participants considered AMU excessive and inappropriate in pig farms in Brazil. However, attitudes towards a restrictive AMU scenario in Brazilian pig farms were predominantly negative, justified by economic, sanitary and social barriers. These included unsatisfactory management and biosecurity conditions in pig farms that, in their opinion, justify AMU to prevent diseases; issues surrounding prescription and acquisition of veterinary drugs; and employment and income relationships arising from the sale of antibiotics. The views of high-level professionals in the Brazilian livestock chain reveal antibiotics as a structural element that enables pig production. Antibiotics were viewed as essential resources for producing cheap food. Foreign markets were considered the most relevant driver of change in AMU practices rather than pressure from Brazilian consumers. A common belief expressed was that AMR is more associated with the inappropriate AMU in human medicine than in the livestock sector. Resistance to change in these stakeholders may hinder the implementation of future public policies to restrict the use of antibiotics in Brazil. Our findings suggest that successful measures to deal with the AMU/AMR challenges in the pig chain shall not be rooted in personal behaviour change. Instead, honest interdisciplinary dialogues and structural changes are needed to define common grounds and a way forward to break the cycle perpetuating antibiotics as structural commodities.